KEMAMPUAN KOMITMEN PROFESIONAL MEMODERASI PENGARUH KOMPLEKSITAS TUGAS DAN KONFLIK PERAN PADA KINERJA AUDITOR - Pratama, I Gusti Putu Angga Rahmita; Latrini, Ni Made Yenni (E-Jurnal Akuntansi; Vol 14 No 3 (2016), 2016)
This research was conducted at the public accounting firm in the area of ??Bali. Samples in this study of 57 respondents to the sampling technique used was purposive sampling. Data collection method used is the method of questionnaires and documentation. Data analysis technique used is the technique of multiple linear regression analysis. Based on the results of research by distributing questionnaires to 57 respondents, it can be concluded that the complexity of the task and a significant negative effect on the performance of auditors and the role of conflict does not have a significant effect on the performance of auditors. Professional commitment proved able to moderate the effect of task complexity and conflict on the performance of auditors.
Keywords: kinerja auditor, kompleksitas tugas, konflik peran, komitmen profesional